The notch and TGF-β signaling pathways contribute to the aggressiveness of clear cell renal cell carcinoma. - Jonas Sjölund; Anna-Karin Boström; David Lindgren; Sugata Manna; Aristidis Moustakas; Börje Ljungberg; Martin Johansson; Erik Fredlund; Håkan Axelson (PLoS ONE, 2011)
BACKGROUND: Despite recent progress, therapy for metastatic clear cell renal cell carcinoma (CCRCC) is still inadequate. Dysregulated Notch signaling in CCRCC contributes to tumor growth, but the full spectrum of downstream processes regulated by Notch in this tumor form is unknown. METHODOLOGY/PRINCIPAL FINDINGS: We show that inhibition of endogenous Notch signaling modulates TGF-β dependent gene regulation in CCRCC cells. Analysis of gene expression data representing 176 CCRCCs showed that elevated TGF-β pathway activity correlated significantly with shortened disease specific survival (log-rank test, p = 0.006) and patients with metastatic disease showed a significantly elevated TGF-β signaling activity (two-sided Student's t-test, p = 0.044). Inhibition of Notch signaling led to attenuation of both basal and TGF-β1 induced TGF-β signaling in CCRCC cells, including an extensive set of genes known to be involved in migration and invasion. Functional analyses revealed that Notch inhibition decreased the migratory and invasive capacity of CCRCC cells. CONCLUSION: An extensive cross-talk between the Notch and TGF-β signaling cascades is present in CCRCC and the functional properties of these two pathways are associated with the aggressiveness of this disease.